Actividad fibrinolitica en venenos de serpientes peruanas de los géneros bothrops, lachesis y crotalus - Collantes, Hugo G. (1992)
We studied the presence of fibrinolytic activity in five dried peruvian snake venoms using fibrin clots formed by one partially purified fraction of Thrombin-like enzyme from L. muta muta. In all venoms studied, fibrinolysis were detected in absence of plasmin in the range from 16,3 to 57,5 U/h mgprotein. This results demonstrate the existence of proteolytic enzymes in Peruvian Viperid snake venoms that act upon fibrin. The L. muta muta venom showed the higher activity (57 ,5), followed in down order by B. barnetti (45,2) B. pictus (29,4), C. durisus terrificus (22,5) and B. brazilü venom (16,3).